Los topónimos con *up- (*op-) “agua, río” en la toponimia prerromana hispana (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The reading IAPPIOPPENSIS in a funerary stele recently discovered   in Famelicão (Portugal) allows the autor of the article to explain etymologically the etnonym [.]APIBICESIS, known long time ago and found in   a near zone. The analysis is used for revise the pre-roman hispanic hidrotoponyms containing the radical *up- (*op-) “water, river”.